Extraction, Phenolic Content and Hydrogen Peroxide Scavenging Capacity of Extracts from Some Honey Samples, Propolis and Bee Pollen - Zohra Mohammedi (Biology, Medicine, & Natural Product Chemistry, 2021)
Honey and propolis is natural food, produced by honey bees (Apis mellifera) and largely used by the local population for its medicinal properties. Our work aims to extract and evaluate the hydrogen peroxide scavenging capacity of different phenolic extracts from some bee products. Phenolic compounds from honey samples, propolis, and bee pollen were extracted by methanol and subjected to radical scavenging activity towards hydrogen peroxide. The results showed the highest values for the total phenolic and total flavonoïd contents in propolis and bee pollen, and a great hydrogen peroxide (H2O2) inhibition (IC50: 0.205 - 2.210 µg/mL) with honey extracts, while sample “multiflower” is the better antioxidant, more than ascorbic acid used as control. The less scavenging activity was observed with the extract from bee pollen (IC50: 39.383 µg/mL). To combat the harmful effects of free radicals, especially reactive oxygen species including hydrogen peroxide, it is important to use phenolic extracts instead of using honey as it is, and extracts from the honey of different types are excellent antioxidants compared to other bee products.